NEUROIMMUNOENDOCRINE REGULATION OF THE SKIN FUNCTIONING - O. A. Bashkina; M. A. Samotrueva; A. K. Azhikova; L. R. Paknnova (Медицинская иммунология, 2019)
The review deals with modern ideas of neuroimmunoendocrine regulation of physiological and pathophysiological processes in skin. The present data are provided which indicate to composite mechanisms of intercellular interactions in complex regulating systems (nervous, immune, endocrine) acting at the level of skin in normal conditions, as well during the posttraumatic period. We describe different modes for participation of endocrine and nervous systems in immunologically induced skin inflammation. The data are provided confirming localization of adrenergic receptors on membranes of immunocompetent cells and leukocytes, on regulatory effects of hypothalamus upon immune functions, about multidirectional actions upon inflammation of sympathetic and parasympathetic nervous system etc.There are sufficient data on promotion of pathophysiological changes and reconstitution processes in the skin due to effects of local immune cells and bioactive substances expressed by them. The course of skin wound regeneration depend on the type of damage, degree and a phase of healing process. Posttraumatic reparative potential of skin is often limited by the infectious processes initiated by local microflora, products of cell disintegration and necrotic tissues. The cause-effect relationship is proven by arising inflammation which is implemented by inclusion of immune protection responses. The increased necrotic area and suppuration of the wound occurs die to inhibition of system of the phagocytizing macrophages. However, activation of this system brings about formation of the connective tissue capsule around the inflammation focus within early terms.We also discuss the issues of reparative skin regeneration which of great medico-social value, in connection with considerable prevalence of traumatic events and their social consequences, followed by expressed cosmetic defects. Evolving neurocognitive problems lead to decreased quality of the patient’s life, development of social disadaptation and further deprivation. The role of nervous system and psychological frustration in genesis of skin manifestations requires future development of the modern scientific direction, i.e., psychodermatology.Understanding of molecular mechanisms regulating the neuroimmunocutaneous interactions offers new prospectives in treatment of some skin diseases, as well as activation of the damaged skin recovery. According to the data presented in the review article, one may conclude on relevance of further studies on reparative potential of skin under interactions of homeostatic regulatory systems.